Mapping mammal diversity in the Central Highlands and South Central Coast of Vietnam - Tran Van Dung,; Phung Thu Cuc, (Journal of Forestry Science and Technology, 2025)
This study constructed and analyzed spatial diversity maps of mammalian species to enrich biodiversity information and assess diversity levels based on the distribution data of mammals in the Central Highlands and South Central Coast of Vietnam. The research utilized mammal spatial distribution maps from the IUCN Red List of Threatened Species as input data. Species maps were overlaid, analyzed, and synthesized using GIS software for comprehensive analysis. Additionally, the study developed a species richness map specifically for threatened mammalian species in the region. Key findings revealed that the Central Highlands and South Central Coast of Vietnam exhibit high mammalian diversity, with 187 species. The area with the highest diversity supports up to 122 species, while the least diverse area includes only 75 species. High-diversity regions are primarily concentrated in the Kon Tum and Da Lat plateaus. Mountainous and plateau regions support greater species diversity, whereas coastal areas exhibit the lowest diversity levels. A total of 64 threatened mammal species were identified within the Central Highlands and South Central Coast regions. The most diverse areas support up to 35 threatened species, while the least diverse areas host 15 species. These findings contribute to the understanding of the region's biodiversity, offering valuable insights to inform conservation planning and the development of effective management strategies.